Effects of hygrothermal, UV and SO2 accelerated ageing on the durability of ETICS in urban environments - Parracha, João L. (2021)
External Thermal Insulation Composite Systems (ETICS) have been extensively used for either new constructions or building facades retrofitting in the last decades. These systems can provide improved thermal performance to the building envelope. However, their long-term durability remains a pervasive concern, with some systems presenting relevant anomalies after few years from their application. The durability assessment of ETICS is defined by the EAD 040083-00-0404 guideline, which stated an accelerated ageing procedure based on the hygrothermal and freeze-thaw behaviour. Nevertheless, further important environmental urban conditions, such as UV radiation and atmospheric pollutants, as well as bio-susceptibility, are not envisaged in the guideline. This paper presents the results of an experimental campaign with the aim of evaluating the durability of the rendering system of several commercially available ETICS exposed to an innovative accelerated ageing procedure, which consists of hygrothermal cycles, UV radiation and air pollutants (SO2) exposure. Physical and chemicalmorphological tests were carried out prior and after each ageing cycle in order to evaluate the durability of ETICS. Biological susceptibility to moulds was also assessed. The experimental results showed that both surface hardness and surface gloss decreased after the combined effect of the hygrothermal, UV, and SO2 ageing cycles, whereas an increase of surface roughness was observed. Substantial colour change for all systems after the ageing procedure was observed, confirming aesthetic alteration. Traces of biological growth were detected on the systems after ageing and the contact angle decreased after the hygrothermal cycles, indicating a lower surface hydrophobicity of the systems.